2018
DOI: 10.1371/journal.pone.0193424
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic analysis of immune activation in equine leptospirosis and Leptospira-vaccinated horses

Abstract: Currently available diagnostic assays for leptospirosis cannot differentiate vaccine from infection serum antibody. Several leptospiral proteins that are upregulated during infection have been described, but their utility as a diagnostic marker is still unclear. In this study, we undertook a lipidomics approach to determine if there are any differences in the serum lipid profiles of horses naturally infected with pathogenic Leptospira spp. and horses vaccinated against a commercially available bacterin. Utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
2
5
0
1
Order By: Relevance
“…Several key sphingomyelins also were increased in the tear film of infected cows (Figure 4), similar to increases in serum sphingomyelins we have reported for the immune response to leptospira vaccination in horses [17].…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Several key sphingomyelins also were increased in the tear film of infected cows (Figure 4), similar to increases in serum sphingomyelins we have reported for the immune response to leptospira vaccination in horses [17].…”
Section: Resultssupporting
confidence: 83%
“…Therefore, standardization of the data based on tear volume was not possible. However, there were no significant differences in the ion intensities of internal standards between samples, and the RSDs for raw peak areas were less than 50%, comparable to previous infection studies where lipid metabolites were normalized to the volume of the analyte [17]. Therefore, semi-quantitative data are presented as the raw peak areas for each of the high-resolution masses.…”
Section: Methodssupporting
confidence: 71%
See 1 more Smart Citation
“…Although Leptospira interrogans serovar Pomona type kennewicki is undoubtedly the predominant Leptospira equine pathogen in North America, L. Grippotyphosa also causes disease in North American horses. Vaccination generally causes low MAT values but some vaccinated horses my have titers as high as those seen with acute infections [71]. There has been concern that vaccination of infected horses with a whole-cell vaccine could theoretically cause ERU or recurrence of signs but this has only rarely been observed and could not be demonstrated in one study [72].…”
Section: Preventionmentioning
confidence: 97%
“…Cyclic phosphatidic acid (cPA) is a lysophospholipid structurally similar to lysophosphatidic acid (LPA), first isolated from the myxamoebae of a true slime mold, Physarum polycephalum , in 1992 [4]. cPA was later found in mammalian tissues and normal and diseased serum [[5], [6], [7], [8], [9], [10]]. We previously reported that cPA attenuates neuropathic pain and neuroinflammation [11,12].…”
Section: Introductionmentioning
confidence: 99%